Differences in ratings of perceived exertion between the sexes during single-joint and whole-body exercise - Springer, B. K.; Pincivero, D. M. (Journal of Sports Sciences, 2010)
The objective of the present study was to examine ratings of perceived exertion (RPE) between adult men (n = 10) and women (n = 10) during two different modes of fatiguing exercise. Participants provided their rating of perceived exertion (6-20 scale) while performing single-leg heel raises and exercise on a rowing ergometer, during two separate experimental sessions. During the heel raise exercise, ratings of perceived exertion were reported for the exercising calf muscles, while a single undifferentiated and two differentiated ratings were obtained during the rowing exercise. Perceived exertion responses were standardized across the exercise duration between participants, via linear interpolation and power function modelling. No significant differences were observed between the sexes in number of heel raises; however, women exercised significantly (P < 0.05) longer during the rowing exercise. No significant differences were observed between the sexes for ratings of perceived exertion obtained via linear interpolation. However, power function modelling revealed greater (P < 0.05) increases for women during the heel raises. The findings of the present study suggest the presence of a subtle difference in the perceived exertion response between the sexes when modelled as a power function during single-joint exercise.